2020
DOI: 10.3389/fgene.2020.00453
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Transcriptional Regulatory Network Associated With Extrathyroidal Extension in Papillary Thyroid Carcinoma by Comprehensive Bioinformatics Analysis

Abstract: Extrathyroidal extension (ETE) affects papillary thyroid cancer (PTC) prognosis. The objective of this study was to identify biomarkers for ETE and explore the mechanisms controlling its development in PTC. We performed a comprehensive bioinformatics analysis using several datasets. Differential expression analysis and weighted gene coexpression network analysis (WGCNA) on 58 paired PTC samples from The Cancer Genome Atlas (TCGA) were used to detect ETE-related mRNA and long noncoding (lnc) RNA modules and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Of note, authors reported no significant change in expression of TINCR in PTC vs. normal tissue, contradicting previous reporting of its upregulation in the same disease [85]. This displays the complexity of lncRNA expression, as well as the varying consequences of their dysregulated expression patterns [86].…”
Section: Papillary Thyroid Cancermentioning
confidence: 79%
“…Of note, authors reported no significant change in expression of TINCR in PTC vs. normal tissue, contradicting previous reporting of its upregulation in the same disease [85]. This displays the complexity of lncRNA expression, as well as the varying consequences of their dysregulated expression patterns [86].…”
Section: Papillary Thyroid Cancermentioning
confidence: 79%
“…Then, the modules whose eigengenes showed correlation above 0.75 (cut line for merging of modules = 0.25) were merged (Y. [5] ), and ten modules were finally obtained. The eigengene adjacency heatmap was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By using TCGA data, reported studies involved to PTC prognostic have shown that long noncoding RNA (lncRNAs), microRNA, and methylation data can work as prognostic factors. Chen et al, using binding motif data from Ensembl Biomart, predicted transcription factors (TFs) for affected genes to construct a TF/lncRNA/mRNA network, which predicted PTC prognosis with an AUC of 0.794 (28). Wang et al established an N6-methyladenosine (m6A) RNA methylation-related risk signature of disease-free survival for a total PTC cohort with an AUC of 0.817.…”
Section: Discussionmentioning
confidence: 99%